Ferroelectric Thin Film Materials Deposition By Physical Vapor Deposition - Chai, Tying Tying (Universiti Sains Malaysia, 2019)
Thin film is a layer of material that has the thickness that ranging from a few nanometers to a few micrometers and have been used in the fabrication of the MEMS devices. The properties of the thin films are affected by the type of the materials and one of the thin film materials is the ferroelectric thin film material. It is a type of material that exhibits polarization without the presence of the electric field. This ferroelectric thin film material is widely used in the fabrication of microelectromechanical systems (MEMS). There are a few manufacturing methods that can apply to the manufacture of MEMS and one of them is the thin film deposition. In this project, the thin film deposition technique used is the powder-based magnetron sputtering. The powder-based magnetron sputtering is different from the conventional magnetron sputtering because the thin film is deposited from the powder target. The deposited thin films are characterized and the electrical properties of the thin films are investigated. The characterization which involved the microstructural analysis and elemental analysis are carried out for the thin film. Overall, the surface of the thin film is smooth, and some may contain contaminant. The electrical properties of the thin films are investigated through the piezoelectric functional test and temperature coefficient of resistance (TCR) test. The piezoelectric coefficient and TCR are the characteristics that needed to consider when designing MEMS devices. The PZT thin films were undergoing piezoelectric functional test and the results indicated that the thin films exhibited piezoelectric effect. In TCR test, the metal thin film (Sb thin film) shows a positive TCR value whereas the non-metal thin film (MgO thin film) shows negative TCR value. There are also some metal thin films such as Ti thin film and Cr thin film that show negative TCR value and this may be due to the presence of the impurities and defects.